Clinical features, comorbidities, complications and treatment options in severe and non‐severe COVID‐19 patients: A systemic review and meta‐analysis - Mohan Giri; Anju Puri; Ting Wang; Shuliang Guo (Nursing Open, 2021)
Abstract Objectives The aim of this analysis was to assess the prevalence of clinical features, comorbidities, complications and treatment options in the patients with COVID‐19 and compare incidence of these clinical data in severe and non‐severe patients. Design Systemic review and Meta‐analysis. Methods PubMed, Embase, Scopus and Web of Sciences databases were searched to identify relevant papers until 20 July 2020. All studies comparing clinical data of severe and non‐severe patients of COVID‐19 were included. Heterogeneity across included studies was determined using Cochrane's Q test and the I2 statistic. Results were expressed as odds ratio with accompanying 95% confidence intervals. Results Twelve studies with 3,046 patients were included. The result showed the most prevalent clinical symptoms were fever 88.3%, cough 62.2%, fatigue 39.5% and dyspnoea 31.5%. Further meta‐analysis showed incidence of fever, cough, fatigue and dyspnoea was higher in severe patients. The most prevalent comorbidities were hypertension 22.6%, diabetes 11.5%, cardiovascular disease 10.3% and cancer 2.5%. We found that compared with non‐severe patients, the symptoms, existing comorbidities and complications are prevalent in severe COVID‐19 patients. Future well‐methodologically designed studies from other populations are strongly recommended.